Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
This chapter outlines my research methodology, which is based on the knowledge gaps identified through an extensive literature search that established the architectural and scientific contexts for my practice. My research questions were formulated under the supervision of Neil Spiller, who guided my architectural design investigations, Martin Hancyzc, who oversaw my chemical studies and Philip Beesley, who I collaborated with in the Hylozoic Ground installation, which informed much of my practical architectural design work. Their continued guidance and support have enabled me to navigate the theoretical and practical aspects of my inquiry. These research questions became the building blocks for further speculative proposals about the possibilities of this multidisciplinary architectural design method and helped me reflect on its broader potential for architectural design practice in the 21st century.